Lexicons of Sugriwa Dance Movements in Wayang Wong Tejakula - Ni Putu Wahyuni; I Gede Budasi; Dewa Ayu Eka Agustini (Institut Agama Islam Negeri Palopo, 2023)
Lexicons and their cultural meaning can be found in Sugriwa dance, Wayang Wong Tejakula. However, the uses of the lexicons and their cultural meaning are rarely used by the dancer from time to time. It can cause language death. This study was designed in the form of a descriptive qualitative method and aimed to find the lexicons and their cultural meaning. The obtained data were collected from observation and interview techniques. The results of the study show that there are 21 lexicons of movements. Those lexicons are categorized into head movements, such as kipekan capung and mengas, body movements, such as agem kanan, agem kiri, matang, nyalin ulat, ngalok-alok, ngadap, ngengsog, and raras, hand movements, such as anyingsing roma, nabdab gelung and ngagen, finger movement that is mudra suara, and leg movements, such as cicangan, dadengkleng, nyeregseg, ngeceb, tanjek kiri, tanjek kanan, and ngeteg. Of those 21 lexicons, only five lexicons have their cultural meaning. Those five lexicons become the characteristic movements of this dance and are classified into three dance stages: tanjek, ngalok-alok and nyeregseg are included in ngugal and have the cultural meaning of introducing the Sugriwa character. Ngengsog is included in pamahbah and has cultural meaning as telling the purpose of Sugriwa to come out to the stage. Ngalok-alok and ngadap are included in ngadap, which has cultural meaning as showing the leadership of Sugriwa's character. The findings and documentation about the lexicons and their cultural meaning in this dance can certainly be teaching material. The dance teachers can easily teach foreigners who want to learn this dance. In addition, it will help students who are interested in learning lexicons and their cultural meanings. In other words, this study can help preserve local languages and avoid language death.